Comparative Analysis of Instagram, Facebook, and TikTok on students Photography Interests in Batam - Jimmy Pratama; Justin Chua (Universitas Internasional Batam, 2024)
Social media is an internet-based platform that allows users the opportunity to interact and present themselves, both in real-time and delayed, to a broad or specific audience, promoting the value of user-generated content and the perception of interaction with others. The research aims to determine the comparison of Instagram, Facebook, and TikTok concerning the photography interest of students in Batam. This study employs a quantitative method by distributing questionnaires to 213 students in Batam. The collected data will be tested using the SPSS 26 application with regression analysis. The results of this research indicate that Instagram has an impact of 34.4%, Facebook has an impact of 33.7%, and TikTok has an impact of 29.5% on students' photography interest.